A study on prevalence of shock among the paediatric age group in and around west Godavari district, Andhra Pradesh. - Sai Silpa Chowday Ch; T Jaya Chandra (Pediatric Review: International Journal of Pediatric Research, 2021)
Introduction: Shock is one of the most common paediatric emergencies with significant mortality. Death is due associated complications and multisystem organ dysfunction. With these a study was conducted to find the prevalence of shock among the paediatric age group.Materials and methods: Study was conducted in the department of paediatrics, ASRAM, Eluru, Andhra Pradesh, over a period of 18 months. Random sampling was considered in this study. Children aged 1 month to 12 years, admitted with clinical diagnosis of shock were included. Neonates and parents of those who didn’t submit the informed consent were excluded. Among the participants, shock was diagnosed by the standard protocol such blood smear examination, inflammatory markers, blood pressure. Chi square test was used to find the association between the variables and P < 0.05 was considered statistically significant.Results: Shock was diagnosed in 75 (7.96%), maximum (39%) were detected in 1 month to 1 year age group.  Gender wise, 41 (54.6) members were male and 34 (45.3) members were female. The male female ratio was 1.2:1. Total 56 (74.6) were survivors and 19 (26.4%) were non survivors; statistically there was no significant difference. Conclusion: Majority of shock cases were in cases were in the age group of >1month to 5 years age group.